The landscape of sea-level rise adaptation resources: Applying grounded theory in California - Daniella Hirschfeld; Kristina E. Hill (Climate Services, 2022)
The threat of climate change caused sea-level rise in coastal areas and the associated consequences for human development are extremely high. Governments and land managers around the world are developing sea-level rise adaptation strategies and physical plans. In this context, the urgency for climate services, meaning the provision of climate information to meet the decision-making needs of users is emerging as a priority. We used a constructivist grounded theory approach to develop an assessment framework and answer the question is there alignment between supplied climate service written guidance materials and the demands of local practitioners working to address sea-level rise in their communities. This framework is highly flexible and compares guidance resources with local actions. We applied this framework in three areas – adaptation barriers, planning processes, and sea-level rise actions – to written climate service materials in California to test its viability and develop policy and theory relevant insights. Through this work we found significant integration of the existing climate services in practice in coastal California. We gained important insights into how climate services can better meet the needs of local practitioners (e.g. by deepening their focus on policy relevant materials). We found that the strategic comparison of different climate change adaptation actions needs more guidance materials. We also found that more explicit support is needed to overcome key policy and legal barriers. We uncovered the fact that newer theories, such as those that create a typology to compare physical sea-level rise adaption strategies have not infiltrated current planning practice and more support is needed to help make the bridge possible. These additional services are essential to ensure the effectiveness of existing resources.